OsSPL88 Encodes a Cullin Protein that Regulates Rice Growth and Development - Chen, Zhengai; Yin, Wenjing; Li, Xuan; Lu, Tao; Ye, Hanfei; Dai, Gaoxing; Mao, Yijian; Li, Sanfeng; Duan, Penggen; Lu, Mei; Rao, Yuchun; Wang, Yuexing (Frontiers in Genetics, 2022)
Plant lesion mimics refer to necrotic spots spontaneously produced by the plant without mechanical damage, pathogen invasion, and adversity stress. Here, we isolated and characterized two rice (Oryza sativa L) mutants, namely, spl88-1 (spotted leaf88-1) and spl88-2 (spotted leaf88-2), which were identified from an ethyl methanesulfonate-mutagenized japonica cultivar Xiushui 11 population. Physiological and biochemical experiments indicated that more ROS accumulated in spl88-1 and spl88-2 than in wild type. spl88-1 and spl88-2 displayed spontaneous cell death and enhanced their resistance to bacterial blight by affecting the expression of defense-related genes. We isolated SPL88 by map-based cloning, which encoded a highly conserved Cullin protein. A single base deletion was detected in spl88-1 and spl88-2, in which the 132nd base C of SPL88-1 and the 381th base T of SPL88-2 were deleted, causing premature termination of protein translation. SPL88 was expressed in root, stem, leaf, leaf sheath, and panicle. The Cullin protein was localized in the cytoplasm and nucleus. The aforementioned results indicate that SPL88 regulates the growth and development of rice by affecting the expression of defense-related genes.